Examining Signatures of Natural Selection in Antifungal Resistance Genes Across Aspergillus Fungi - dos Santos, Renato Augusto Corrêa; Mead, Matthew E.; Steenwyk, Jacob L.; Rivero-Menéndez, Olga; Alastruey-Izquierdo, Ana; Goldman, Gustavo Henrique; Rokas, Antonis (Frontiers in Fungal Biology, 2021)
Certain Aspergillus fungi cause aspergillosis, a set of diseases that typically affect immunocompromised individuals. Most cases of aspergillosis are caused by Aspergillus fumigatus, which infects millions of people annually. Some closely related so-called cryptic species, such as Aspergillus lentulus, can also cause aspergillosis, albeit at lower frequencies, and they are also clinically relevant. Few antifungal drugs are currently available for treating aspergillosis and there is increasing worldwide concern about the presence of antifungal drug resistance in Aspergillus species. Furthermore, isolates from both A. fumigatus and other Aspergillus pathogens exhibit substantial heterogeneity in their antifungal drug resistance profiles. To gain insights into the evolution of antifungal drug resistance genes in Aspergillus, we investigated signatures of positive selection in 41 genes known to be involved in drug resistance across 42 susceptible and resistant isolates from 12 Aspergillus section Fumigati species. Using codon-based site models of sequence evolution, we identified ten genes that contain 43 sites with signatures of ancient positive selection across our set of species. None of the sites that have experienced positive selection overlap with sites previously reported to be involved in drug resistance. These results identify sites that likely experienced ancient positive selection in Aspergillus genes involved in resistance to antifungal drugs and suggest that historical selective pressures on these genes likely differ from any current selective pressures imposed by antifungal drugs.